Wishes of Children With ADHD - Furukawa, Emi; Uchida, Ryoko; Tatsuki, Miho Otomo; Fitts, Margaret; Tripp, Gail (Frontiers in Psychiatry, 2022)
Understanding the desires and motivations of children with ADHD is important in helping them thrive. Their inner worlds, however, have not been well captured. The Three Wishes task provides minimal cues and structure to elicit their desires and hopes in an unbiased manner. The wishes of 299 school-aged children with ADHD (193 boys, aged 6-12) were elicited during a research diagnostic assessment. We developed a coding scheme to characterize different aspects of their wishes, including beneficiary, valence, and immediacy. Maslow’s hierarchy of needs, adapted to take account of the participants’ ages, was used to identify the motivations underlying the children’s wishes. As expected, many of the wishes reported were for immediate fulfillment, with many reflecting material desires. Affiliative wishes, highlighting the children’s desire for positive interpersonal relationships, were also common. There was some evidence for self-actualization/self-betterment goals and a small number of altruistic wishes. A word cloud presents the content of the children’s wishes grouped according to this hierarchy. This study highlights the diversity and typicality of the self-reported needs, desires and hopes of children with ADHD. It also serves as a timely reminder of the value of seeking such information directly from children themselves.